Improving the Attention Performance in High-Functioning Autistics during Memorization Lesson through Neurofeedback Training Approaches - Jafar, Nur Madihah; Jomhari, Nazean; Mohd Yusoff, Mohd Yakub @ Zulkifli (Jurnal Usuluddin, 2019)
Most students with high-functioning autism have difficulties in paying attention that may affect in memorizing lesson material which will impede their learning progress. Several researches have shown that neurofeedback training (NFT) is successful in training the autistics’ attention performance. Thus, the purpose of this study is to measure and compare the effectiveness of two versions of an invention using different NFT approaches on the attention performance of high-functioning autistic (HFA) during memorization of the lesson material. The results from this study showed that the ratio of students those categorized in high attention increased from 3:10 to 4:5 when using the version 2 learning tool which resulted in more effective in improving the HFAs’ attention performance. The findings of this study suggested that the invention of memorization tool was effective for the purpose of enhancing the HFAs’ attention performance during memorization lesson with the adaptation of NFT approaches; visual feedback, audio feedback, verbal response, and reward system.